Effect of torrefaction on palm oil waste chemical properties and kinetic parameter estimation - Nur Hazirah Huda, Mohd Harun; Fakhrur Razil Alawi, Abdul Wahid; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (Italian Association of Chemical Engineering - AIDIC, 2017)
In Malaysia, palm oil wastes are identified as the potential biomass for renewable energy sources. However, biomass is more challenging to utilise as compared to coal. Usually palm oil wastes suffer from a low heating value, low bulk density and their ability to absorb moisture from the surrounding atmosphere increase the costs of thermochemical conversion due to the drying stage. One of the widely-used methods that can be applied as a pre-treatment step to improve biomass properties is torrefaction. Torrefaction involves heating of biomass to moderate temperatures typically between 200 °C and 300 °C in an inert condition. This study aims to investigate on how torrefied biomass properties exhibit on different torrefaction temperature. The effect of torrefaction at four different temperatures (240 °C, 270 °C, 300 °C and 330 °C) were evaluated in term of mass yield, energy yield and higher heating value on two different palm oil wastes which are empty fruit bunch (EFB) and palm kernel shell (PKS). The results show that temperature had significant effect on chemical properties of torrefied biomass as well as affecting the biomass degradation. In addition, the properties of biomass also affect the torrefaction. Overall, EFB shows higher decomposition percentages compared to PKS. PKS has a higher heating value compared to EFB due to the high carbon content of PKS. A two-step reaction in series namely Di Blasi and Lanzetta Model is used to model the anhydrous weight loss (AWL) of EFB and PKS. In the model, the kinetic parameters are estimated by using Arrhenius equation. It shows that the model mass loss data fit well with experimental data at 240 °C but not at 300 °C. This is due to the other factors such as heat transfer effect which is not included in the proposed model. The Di Blasi and Lanzetta model is reliable to be applied in predicting anhydrous weight loss (AWL) of EFB and PKS at lower temperature.